nCx⋅px⋅(1−p)n−x
llllllllllllllllllllllllllllllllllllll
Answer:
x+27
Step-by-step explanation:
Let's simplify step-by-step.
4(x+3)+3(5−x)
Distribute:
=(4)(x)+(4)(3)+(3)(5)+(3)(−x)
=4x+12+15+−3x
Combine Like Terms:
=4x+12+15+−3x
=(4x+−3x)+(12+15)
=x+27
Hope you find this Useful!
Answer:
Step-by-step explanation:
interchange x and y
y= 1/(x - 2)
x = 1 / (y - 2) Multiply both sides by y - 2
x(y - 2) = 1 Remove the brackets
xy - 2x = 1 Add x to both sides
xy = 1 + 2x Divide by x
y = (1 + 2x)/x
The brackets have been destroyed. The answer is as I've given it.
y = (1/x) + 2
Answer:
3
Step-by-step explanation:
9 x (N + 2) = 45
9N + 18 = 45
9N = 27
N = 3
1/4x -2 = -6 + 5/12x
3x - 24 = -72 +5x
3x -5x = -72 +24
-2x = -48
x = 24